"Oh, my god! My season is over!" COVID-19 and regulation of the psychological response in Spanish high-performance athletes - González-Hernández, J.; Lopez-Mora, C.; Yüce, A.; Nogueira-Lopez, A.; Tovar-Galvez, M. I. (Frontiers in Psychology, 2021)
Background: In an unprecedented situation of interruption of the sporting dynamics, the world of sport is going through a series of adaptations necessary to continue functioning despite coronavirus disease 2019 (COVID-19). More than ever, athletes are facing a different challenge, a source of discomfort and uncertainty, and one that absolutely alters not only sports calendars, but also trajectories, progressions, and approaches to sports life. Therefore, it is necessary to identify the levels of psychological vulnerability that may have been generated in the athletes, because of the coexistence with dysfunctional responses during the COVID-19 experience, and which directly influence the decrease of their mental health.